2002
DOI: 10.1080/1071576021000016418
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum Hydroxyl Radical Scavenging Activity in Erythropoietin Therapy Resistant Renal Anemia

Abstract: Relation between anemia resistant to recombinant human erythropoietin (rHuEPO) therapy and the oxidative stress in hemodialysis (HD) patients was investigated. Stable HD patients who had consistent hemoglobin concentrations on a constant dose of rHuEPO were studied. Patients were excluded if there were factors that might affect hemopoiesis or administration of antioxidant supplements. Patients were classified into three groups: High (9000 U/week), Low (1500-4500 U/week) and No rHuEPO group. Thiobarbituric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…In this study we clearly demonstrated that EPO treatment prevents the formation of peroxynitrite. This finding regarding the effects of EPO on free radical production is consistent with the results of previous studies (42)(43)(44).…”
Section: Discussionsupporting
confidence: 93%
“…In this study we clearly demonstrated that EPO treatment prevents the formation of peroxynitrite. This finding regarding the effects of EPO on free radical production is consistent with the results of previous studies (42)(43)(44).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, EPO treatment prevented the formation of tissue nitrotyrosine staining in DNBS-treated animals. This result of the effects of EPO on free radical production is in agreement with previous studies (Squadrito et al, 1999;Hirayama et al, 2002). Superoxide and peroxynitrite cause DNA single-strand damage, leading to poly(ADPribose) synthetase activation and cell death (Szabo and Dawson, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Signal intensities of the hydroxyl radical spin adducts were measured using electron spin resonance (ESR) according to a method previously described [24]. ESR spectra were obtained by JEOL TE-25X ESR equipment (JEOL, Tokyo, Japan) and 5,5-dimethyl-1-pyrroline N-oxide (DMPO) was used for a spin-trapping reagent.…”
Section: Methodsmentioning
confidence: 99%